DAMPAK RELOKASI PASAR RAKYAT SENTRAL BISNIS DISTRIK KABUPATEN PULAU MOROTAI - Asar, Umulfatia; Hasan, Nonce; Kotib, Mohammad (Journal of Applied Management and Accounting Science, 2024)
To determine the impact of market relocation on the income of Central Business District (CBD) People's Market traders, Morotai Island Regency 2. To determine the impact of market relocation on the business capital of Central Business District (CBD) People's Market traders, Morotai Island Regency Research Objectives 1. How The impact of market relocation on the income of Central Busness District (CBD) People's Market, Morotai Island Regency. 2. What is the impact of market relocation on business capital at the Central Busness District (CBD) People's Market, Morotai Island Regency? Data analysis in this research uses descriptive qualitative methods in analyzing the data where researchers go directly into the field to obtain data from the beginning to the end of the research. Then the data obtained through interviews with informants is described thoroughly. namely by describing the facts and circumstances that occur in the subject and research information to obtain conclusions. the impact of market relocation in the Central Busness District (CBD) People's Market, Morotai Island Regency, the impact on traders who experienced a decrease in income, the impact of the Central Busness District (CBD) People's Market relocation, resulting in traders experiencing problems in spending business capital. 1. After the market relocation at the Pasar Rakyat Central Busness District (CBD) Morotai Island Regency market, the impact on traders experienced a decrease in income, because the location used for relocation was less strategic, far from residential areas. 2. After the relocation at the Central People's Market market Busness District (CBD) Morotai Island Regency, the impact on traders who have business capital constraints is due to the fact that the number of traders' income has decreased more.